Does moral anti-theodicy beg the question? - Echazú, Gabriel (International journal for philosophy of religion, 2024)
Some philosophers of religion have argued that moral anti-theodicy begs the question. This paper evaluates the arguments from two such philosophers, writing a decade apart—Robert Mark Simpson, and Lauri Snellman. Simpson argues that any global argument against theodicy must allow for the possibility of there existing a plausible theodicy, and that anti-theodical arguments (the argument from insensitivity, the argument from detachment, and the argument from harmful consequences) all implicitly discount this possibility, thus ending up begging the question. Snellman argues that moral anti-theodicies presuppose that some evils cannot be justified, which would presuppose that theodicy is false from the start, which in turn would beg the question against theodicy. The author of the paper argues that Simpson’s arguments rest on an erroneous assumption regarding the nature of anti-theodicy, and that one of Simpson’s arguments sets a problematic standard for argumentation that the author argues we should not accept. It is also argued that Snellman’s argument relies on an unsupported claim from Toby Betenson. Therefore, the author concludes that Simpson and Snellman have not managed to show that moral anti-theodicies beg the question.